Discourse Analysis of Grammatical Cohesion Devices in College Students’ Academic Writing Essay - Yuliani Trisnaningrum; Alek Alek; Didin Nuruddin Hidayat (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
ABSTRACTThe study was undertaken to investigate grammatical cohesion devices use in college students’ academic writing essay as a part of discourse analysis. The study also explored to find out the kinds of grammatical cohesion devices specifications in college students’ academic writing essay. The researchers conducted this study with attention to know the college students’ writing quality at tertiary education. Further, the researchers employed Halliday & Hasan (1976) conceptual framework related to grammatical cohesion devices. The study was conducted to 42 college students enrolling on an online writing course. The researchers applied descriptive and analytical study by giving an assignment to assess grammatical cohesion devices use in college students’ academic writing essay. Data were collected from college students’ academic writing essay. The findings revealed that 1048 grammatical cohesion devices were used in the essays. Other findings indicated that the highest use of grammatical cohesion devices were reference with 53.53% and conjunction. The data also pointed out that the college students were more familiar with reference and conjunction use rather than substitution and ellipsis. The result also indicated that the lack of grammatical cohesion devices use in terms of comprehension, knowledge and ability in writing leads the college students use inappropriate grammatical cohesion devices.ABSTRAKPenelitian ini bertujuan menginvestigasi penggunaan perangkat grammatical cohesive device/kohesi tata bahasa pada penulisan akademik esai mahasiswa. Penelitian ini juga bermaksud untuk menggali jenis-jenis spesifikasi kohesi tata bahasa pada esai mereka. Dalam penelitian ini, para peneliti ingin mengetahui kualitas penulisan esai mahasiswa di perguruan tinggi. Untuk mencapai tujuan tersebut, para peneliti menggunakan kerangka konseptual dari Halliday dan Hasan (1976) terkait dengan kohesi tata bahasa. Penelitian ini melibatkan 42 mahasiswa yang mengikuti kelas menulis via daring. Penelitian menggunakan studi deskriptif dan analitik dengan menugaskan para mahasiswa menulis esai. Temuan dari penelitian ini menunjukkan bahwa terdapat 1048 kohesi tata bahasa yang dipergunakan dalam esai-esai tersebut. Selanjutnya, temuan lain menunjukkan bahwa penggunaan kohesi tata bahasa tertinggi adalah referensi 53,53% dan kata penghubung 45,80%. Temuan lainnya adalah mahasiswa lebih familiar terhadap dua aspek tersebut daripada substitusi dan elipsis. Hasil penelitian juga menunjukkan bahwa kurangnya tata kohesi bahasa dalam hal pemahaman, pengetahuan, dan kemampuan dalam menulis menyebabkan para mahasiswa menggunakan tata bahasa kohesi yang kurang variatif. How to Cite: Trisnaningrum, Y., Alek, Hidayat, D. N. (2019). Discourse Analysis of Grammatical Cohesion Devices in College Students’ Academic Writing Essay . IJEE (Indonesian Journal of English Education), 6(1), 79-90. doi:10.15408/ijee.v6i1.12502